Mental health indicators for children and adolescents in OECD countries: a scoping review - Deckert, Andreas; Runge-Ranzinger, Silvia; Banaschewski, Tobias; Horstick, Olaf; Elwishahy, Abdelrahman; Olarte-Peña, Margarita; Faber, Claudia; Müller, Thomas; Brugnara, Lucia; Thom, Julia; Mauz, Elvira; Peitz, Diana (Frontiers in Public Health, 2024)
Background: This scoping review is a further step to build up the Mental Health Surveillance System for Germany. It summarizes and analyzes indicators used or described in OECD Organisation for Economic Co-operation and Development (OECD) countries for public mental health monitoring in children and adolescents aged 0-18 years.We searched PubMed-MEDLINE, PsycINFO, Cochrane Databases, and Google Scholar from the year 2000 to September 2022. The search used five general keyword categories: 1) "indicators/monitoring/surveillance" at the population level, 2) "mental/psychological", 3) ""health/disorders", 4) "children and adolescents", and 5) 38 OECD countries. The search was complemented with an extensive grey literature search including OECD public health institutions, and an internet search using Google. A predefined set of inclusion and exclusion criteria was applied.Results: Over 15 500 articles and documents were screened (scientific search N=10 539, grey literature search more than 5000). More than 700 articles and documents have been full text assessed, with 382 being ultimately included. Out of 7 477 indicators that have been extracted, an initial set of 6 426 indicators met our inclusion criteria for indicators. After consolidating duplicates and similar content, this initial set was categorized into 19 topics, resulting in a final set of 210 different indicators. The analysis highlighted an increasing interest in the topic since 2008, but indicators for the younger age, particularly those aged 0 to 2 years, were less readily available.Our research provides a comprehensive understanding of the current state of mental health indicators for children and adolescents, identifying both 1) Indicators of public mental health noted in a previous scoping review on adults and 2) New indicators specific to this age group. These findings contribute to the development of effective public health surveillance strategies for children and adolescents and inform future research in this field.